Technical and Vocational Education and Technology Transfer: Departments of Civil Engineering Technology at the Public Authority for Applied Education and Training, PAAE&T, Kuwait, As A Case Study - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Technology transfer is the main ingredient of technical and vocational education. The transfer of know-how and know-why can take several forms either within technical and vocational institutions boundaries such as: transfer of technology from research and development department to other academic departments or interactions and exchange of technology between academic departments. The transfer of technology can transcend technical and vocational institutions boundaries to allow a free transformation and exchange of technology with local and international industries and business. The main objective is to enhance the quality of technical and vocational graduates as well as to provide industries and business with the require skilled and semi-skilled manpower able to managing, maintain, adapt, and monitor the technology applied in various production processes. Therefore, for a successful transfer of technology, a mutual interest has to be achieved for both parties (the provider of technology and the recipient of technology). The management of technical and vocational education must exert their time and efforts to gain the best fruitful results from the transfer of technology in enhancing their academic capabilities (e.g., upgrading the standard of workshops and laboratories, applying and effective scheme for reviewing and assessing curriculum development, enhancing staff competencies) in order to meet the quality assurance standard in producing a high quality of graduates. In this paper, I present some of the empirical results and observations which describe the interactions between the supplier of technology (Civil Engineering Technology) and the recipient of the technology (PAAE&T) in the field of technology transfer. In other word, whether the PAAE&T have taken the opportunity, while building its new headquarter, in the transfer of technology from the supplier Civil Engineering Technology to its academic staff in its various Civil Engineering Academic Departments in its various colleges and institutions. The paper argues that, for effective and efficient transfer of technology, the recipient (PAAE&T) must ensure that the agreement with the supplier of Civil Engineering Technology include calluses that would allow the PAAE&T academic staff in the Civil Engineering Academic Departments in its various colleges and institutions to acquire the technology embedded in the agreement. The paper concludes that the transfer of technology and the building of a local scientific and technical infrastructure must be viewed by Kuwaiti decision-makers as a complementary to one another. Thus, reducing, to great extent, the level of dependence on expatriate, particularly in essential sector of the economy.